Submental Intubation Including Extubation: Airway Complications of Maxillomandibular Fixation - Santosh Kumar Yadav; Gopendra Deo (Case Reports in Anesthesiology)
Hernandez first described the submental route for endotracheal intubation in 1986 as an alternative airway maneuver for maxillofacial procedures. Since that time, several case studies have been performed demonstrating the efficacy of the submental approach. This method was recently implemented in the case of a patient with altered nasal anatomy who sustained a mandibular fracture necessitating maxillomandibular fixation. Unlike most of the cases described in the literature, this patient’s operative course was confounded by the need to extubate through the submental tunnel. The patient tolerated the procedure well and was able to avoid other forms of surgical airway.